Evaluasi Hasil Analisis FEM Manual dan Komputasi pada Struktur Rangka Ruang dan Portal 3D: Studi Literatur - Yuliawana, Elsa; Ali, Dang Fadhlan (Dept. of Civil Engineering Universitas Riau, 2024)
The Finite Element Method (FEM) is essential for analyzing complex structures, but a knowledge gap exists regarding result differences found between transparent manual/script methods (Excel, MATLAB) and automated commercial software (SAP2000, ETABS). This comparison is vital to address the need for transparent validation practices, especially for learning and design optimization. This study's objective is to compare key FEM outputs (nodal displacements, member forces, support reactions) using a literature review with a descriptive-analytic method. Main findings show two patterns: high consistency (results reported as